Contextualizing Arabic Language Instruction: Assessing the Effectiveness of Learning Outcomes through Contextual Teaching and Learning among Secondary School Students - Erika, Endang; Rahmaini, Rahmaini (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2026)
Improving students' achievement in Arabic language learning remains a significant challenge in Islamic secondary schools. Contextual Teaching and Learning (CTL) has been widely recognized as an effective learner-centered approach; however, evidence regarding its effectiveness in Arabic language instruction remains limited. This study examined the effect of the CTL strategy on Arabic language learning outcomes among class VIII students at MTs Nahdlatul Muslimin Pantai Labu. A quasi-experimental design was employed involving 50 students, consisting of 24 students in the experimental class and 26 students in the control class. Data were collected through achievement tests and analyzed using descriptive and inferential statistics. The Shapiro–Wilk test indicated that the data were not normally distributed (experimental class: p = 0.031; control class: p = 0.006); therefore, the Mann–Whitney U test was applied. The findings revealed that the experimental class achieved a substantially higher mean score (78.92) than the control class (33.08). The Mann–Whitney U test showed a significant difference between the two groups (U = 8.000, Z = -5.934, p < 0.001), with a large effect size (r≈0.84). These findings demonstrate the effectiveness of CTL in improving Arabic language learning outcomes and support its broader implementation in Arabic language education at the madrasah level.